2021
DOI: 10.1371/journal.pone.0245446
|View full text |Cite
|
Sign up to set email alerts
|

Arachis hypogaea resveratrol synthase 3 alters the expression pattern of UDP-glycosyltransferase genes in developing rice seeds

Abstract: The resveratrol-producing rice (Oryza sativa L.) inbred lines, Iksan 515 (I.515) and Iksan 526 (I.526), developed by the expression of the groundnut (Arachis hypogaea) resveratrol synthase 3 (AhRS3) gene in the japonica rice cultivar Dongjin, accumulated both resveratrol and its glucoside, piceid, in seeds. Here, we investigated the effect of the AhRS3 transgene on the expression of endogenous piceid biosynthesis genes (UGTs) in the developing seeds of the resveratrol-producing rice inbred lines. Ultra-perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…We processed the raw data of RNA-seq by the methods described by Lee et al [48]. Briefly, the raw data were quality trimmed using the Cutadapt software with parameters: -a AGATCGGAAGAGC-A AGATCGGAAGAGC-q 30 -m 20 [49], and the trimmed data were mapped to a reference rice genome, MSU7 (http://rice.uga.edu/) using the HISAT2 software [50] with default parameter (S1 Table ).…”
Section: Total Rna Extraction and Rna-seqmentioning
confidence: 99%
See 1 more Smart Citation
“…We processed the raw data of RNA-seq by the methods described by Lee et al [48]. Briefly, the raw data were quality trimmed using the Cutadapt software with parameters: -a AGATCGGAAGAGC-A AGATCGGAAGAGC-q 30 -m 20 [49], and the trimmed data were mapped to a reference rice genome, MSU7 (http://rice.uga.edu/) using the HISAT2 software [50] with default parameter (S1 Table ).…”
Section: Total Rna Extraction and Rna-seqmentioning
confidence: 99%
“…As described by Lee et al [48], we synthesized cDNA using the iScript TM cDNA Synthesis Kit (Bio-Rad, Hercules, CA, USA) from 1 μg of each total RNA taken in total RNA samples with three replicates of Dongjin, Geonganghongmi, Jeokjinju, Boseokheukchal, Heukjinju, Heukjinmi, and Heukseol. We carried out quantitative real time-polymerase chain reaction (qRT-PCR) with cDNA and the primer sets listed in the S3 Table in the CFX96 TM Real-Time Detection System (Bio-Rad, Hercules, CA, USA) using iQ SYBR Green Supermix (Bio-Rad, Hercules, CA, USA).…”
Section: Gene Expression Analysis By Quantitative Real Time-polymeras...mentioning
confidence: 99%
“…In transgenic Arabidopsis , overexpression of one RS gene from P. cuspidatum increases the accumulation of trans-piceid in the stilbene biosynthetic pathway and enhances resistance against Colletotrichum higginsianum [ 53 ]. RS is an STS, and resveratrol-forming STS genes have been identified in a variety of plant species, including mulberry [ 54 ], groundnut [ 55 ], and grapevine [ 50 ]. Unfortunately, there are few relevant reports related to the functions of RS and CHS in F. multiflora [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified and characterized members of CHS and STS gene families in peanut (A. hypogaea), whereas there have been no reports on these families on wild Arachis species [43][44][45][46]. The allopolyploid domesticated peanut, with an AABB genome, arose from natural hybridization between the diploid ancestors A. duranensis (genome A) and A. ipaënsis (genome B), followed by spontaneous chromosome duplication [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that resveratrol, besides its classical role as antimicrobial phytoalexin, constitutes an important regulator for the initiation of a hypersensitive response (HR) cell death, as described for A. stenosperma against M. arenaria [58,63,64]. Overexpression of STS genes isolated from cultivated peanut has already been reported in transgenic sweet potato and rice, both aiming to produce resveratrol in heterologous systems [17,45,46]. To our knowledge, the present study is the first report that applies the heterologous overexpression of an STS gene to increase nematode resistance, providing new functional insights into its role in biotic stress responses.…”
Section: Discussionmentioning
confidence: 99%